Potensi Karbon Aktif Kulit Pisang Kepok (Musa Acuminate L) Dalam Menyerap Gas CO Dan SO2 Pada Emisi Kenderaan Bermotor - Sari Wardani; Elvitriana .; Vera Viena (Jurnal Serambi Engineering, 2018)
This study aims to study the efficiency of CO and SO2 gas absorption in motor vehicles emission using activated banana leather bark (Musa acuminate L). The carbon was prepared though consists of a banana skin carbonation process at a temperature at 450 o C for 1.5 hours and activated carbon activation process using H2 SO4 activator at concentrations of 1 Nfor 1, 2 and 3 hours.The motor vehicle emission absorption process uses an adsorption tube which has been loaded activated carbon and connected to the exhaust for 5 minutes. The test of activated carbon characteristics studied were absorption test I2, FTIR test and SEM test. The results showed that iodine absorption was 914 mg / g. The FTIR spectra of activated carbon showed absorption band spectra at wave number 781,17 - 3624,25 cm-1 on vibration of group -OH, with intensity 77,85%. The SEM results show the addition of pore size before and after activation of 1.131 μm and 15.015 μm. The carbon CO gas absorption efficiency is 25% and Gas SO2 is 40%